Cerebral Arterial Thrombosis in Ulcerative Colitis - Giovanni Casella; Claudio Camillo Cortelezzi; DeLodovici Marialuisa; Princiotta Cariddi Lucia; Verrengia Elena Pinuccia; Vittorio Baldini; Sergio Segato (Case Reports in Gastrointestinal Medicine)
Thrombosis, mainly venous, is a rare and well-recognized extraintestinal manifestation of inflammatory bowel disease (IBD). We describe a 25-year-old Caucasian man affected by ulcerative colitis and sclerosing cholangitis with an episode of right middle cerebral arterial thrombosis resolved by intraarterial thrombolysis. We perform a brief review of the International Literature.